(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Exclusive breastfeeding is one of strategies which promote growth of infants by preventing to them several health problems. Therefore, many factors may foster or hinder this measurement which is beneficial not only to the health of the infant but also to the health of the mother. So, the study aimed at identifying Unfavoring factors for Exclusive breastfeeding in the Albert Bartel health area, in Goma. A cross-sectional study was conducted on a sample of 259 breastfeeding women on whom the survey focused. After data collection, processing and analysis, the following factors were found significantly unfavorable for exclusive breastfeeding, namely: the illiteracy [P-value: 0.004; 95% CI: 0.01093385-0.05489074], the household size of 6 and more, [ P-value: 0.047; 95% CI: 0.4203445 - 0.5453086], the refusal to breastfeed on the grounds of preventing breast deformation [P-value: <0.001; 95% CI: 0.1160577- 0.2085643], the parity. [P-value: 0.020; 95% CI: 0.4432101- 0.5682389], the breast diseases during breastfeeding [P-value: 0.022; 95% CI: 0.06344411-0.1391888] and Prenatal education. [P-value: 95% CI: <0.001; 0.2713317-0.3890251]. The study recommends that local leaders take into consideration these different factors concerning health education within health facilities and in the community.